How often segmentectomy is feasible in lung cancer surgery: a population-based evaluation. (4th August 2021) - Helminen, Olli; Söderström, Johan; Andersen, Heidi; Sihvo, Eero
Abstract:  : OBJECTIVES: Despite promising outcomes in lung cancer surgery, segmentectomy has not gained wide acceptance at the population level. Our aim was to evaluate the potential role of segmentectomy in real-world practice. METHODS: All patients diagnosed with lung cancer and operated between January 2013 and December 2019 in Central Finland and Ostrobothnia were included. This intent-to-treat analysis sub-grouped segmentectomy patients by indications: (i) high-risk patients with stage I disease ( n  = 40), (ii) ≤20 mm ground-glass opacity ( n  = 12), (iii) carcinoid ( n  = 12), (iv) special indication ( n  = 20) including synchronous and metachronous disease, fissure-crossing tumour, and synchronous other solid cancers requiring surgery, (v) solid ≤2 cm tumour ( n  = 14) in medically fit patient. To evaluate the potential role of segmentectomy, all preoperative CT scans were re-evaluated. RESULTS: Of 269 patients, in 98 (36.4%) intention of surgery was segmentectomy. Indication was high risk in 40 (14.9%), ground-glass opacity in 12 (4.5%), carcinoid in 12 (4.5%), special indication in 20 (7.4%) and ≤2 cm solid tumour in medically fit patients in 14 (5.2%). The major complication rate was ≤15% in all groups with excellent 3-year recurrence-free survival between 76.5% and 100%. Segmentectomy could have been technically potential in up to 46.8% of patients. This was exactly the rate performed in the last 3-year period of this study. CONCLUSIONS: Performed and potential segmentectomy rates underline the importance of adaptation of this technique with possibility to offer curative surgery to many high risk and special patients with low morbidity and mortality. Abstract : Lung cancer is the leading cause of cancer mortality worldwide [1].